2001
DOI: 10.1071/pp01023
|View full text |Cite
|
Sign up to set email alerts
|

Role of membrane transport in phloem translocation of assimilates and water

Abstract: Most growth and storage organs (sinks) of higher plants import assimilates in solution by bulk flow through the phloem, driven by differences in hydrostatic pressure. These differences in pressure, located between the ends of the interconnecting phloem path, are generated by osmotic water movement, driven in turn by membrane transport of solutes. Sucrose, amino-nitrogen compounds and potassium represent the osmotically important solutes found in phloem contents of most species. Phloem loading and unloading eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 129 publications
2
74
0
1
Order By: Relevance
“…In the model, such processes occur for each internode and rachis. The leakage mechanism is associated to a diffusion process, and is modeled by a linear function of the carbohydrate phloem concentration, since the apoplastic concentration is very low (Patrick et al, 2001): Leakagei=Fresh MassikCphloem…”
Section: Methodsmentioning
confidence: 99%
“…In the model, such processes occur for each internode and rachis. The leakage mechanism is associated to a diffusion process, and is modeled by a linear function of the carbohydrate phloem concentration, since the apoplastic concentration is very low (Patrick et al, 2001): Leakagei=Fresh MassikCphloem…”
Section: Methodsmentioning
confidence: 99%
“…The paralleled expression patterns of CscwINV and CsHT3 during cucumber fruit enlargement suggested that cell wall invertases regulate phloem unloading in cucumber fruit and produce hexose that may be transported in phloem parenchyma cells by HTs. Cell wall invertases are thought to be involved in phloem unloading in some sink organs before [56,57]. However, none of CsHT2, CsHT3 or CsHT4 could transport fructose.…”
Section: The Role Of Hexose Transporters and Cell Wall Invertases In mentioning
confidence: 97%
“…Cell size in rapidly expanding cucumber fruit were shown to increase 10-fold in 4 days [35], which requires the continuous support and availability of abundant sugars. Invertase enzymes can hydrolyze sucrose to hexose monomers, which supports phloem unloading in fruits by maintaining a sucrose gradient between the end of the phloem path and unloading sites [57].…”
Section: The Role Of Hexose Transporters and Cell Wall Invertases In mentioning
confidence: 99%
“…There is also promising research that suggests that phloem may also play a role in repairing embolisms by providing the sugars used to generate the osmotic potential to refill vessels (Salleo et al 1996(Salleo et al , 2004Zwieniecki et al 2000). Additionally, when sugars exit the phloem, the osmotic potential of the phloem drops and the surplus water that originally transported the sugars could be used for refilling (Milburn 1996;Patrick et al 2001). The vascular bundle structure of monocots puts the phloem tissue in close proximity to xylem conduits, making it plausible that the phloem could play a direct role if xylem conduits were to become embolized.…”
Section: Comparisons Between Speciesmentioning
confidence: 95%